Peningkatan Minat Siswa dalam Meneliti Sejarah Lokal melalui Program Kunjungan Museum Perjuangan Rakyat Jambi - Wahyudi, Chairul (LPTK IAIN Kediri, 2023)
This study aims to determine the effect of the Museum Perjuangan Rakyat Jambi on interest in researching local history for MAN Insan Cendekia Jambi students. This research is useful to be a reference material for related parties in optimizing the role and function of museums and increasing interest in research among students, especially in history subjects. This research is a quantitative research with a qualitative approach. Data was collected using observation, interview and questionnaire steps. The data analysis technique used in this research is percentage analysis with the formula P = f / N x 100%. Furthermore, the data were analyzed using the Miles and Huberman model with the steps of Data Condensation, Data Display and Conclusion drawing / verification. The research sample was taken using the Slovin technique with a population of 115 people and a sample of 35 people. The results showed that the Jambi People's Struggle Museum had an effect of 83.42% on the interest in researching the local history of Jambi MAN Insan Cendekia students. Of the 15 statement items given to respondents, 10 statement items received very good qualifications, 4 statement items were classified as good qualifications and only 1 statement item was included in the deficient category. So it can be concluded that the Jambi People's Struggle Museum has a very good effect on the interest in researching local history of Jambi MAN Insan Cendekia students.